Effect of cation distribution on structural and magnetic properties of Dy substituted magnesium ferrite - Bamzai, K. K.; Kour, Gurbinder; Kaur, Balwinder; Kulkarni, S. D. (Journal of Magnetism and Magnetic Materials, 2013)
Magnesium ferrite and dysprosium (Dy3+) substituted with composition MgDyxFe2-xO4 (x = 0.00-0.07) was prepared by solid state reaction technique. Spinel phase formation was identified using x-ray diffraction technique, thus establishing the cubic spinel symmetry. The morphology was seen through scanning electron microscopic technique, from where the grain size was calculated using average intercept line method. The elemental composition of pure and dysprosium substituted magnesium ferrite was calculated from energy dispersive x-ray analysis spectrum which is then correlated with the experimentally obtained values. Magnetic hysteresis loop of the various compositions establishes it to be soft ferrimagnetic material. The magnetic parameters such as saturation magnetization, coercivity, and retentivity were also calculated. Temperature dependence of saturation magnetization was done to find the Curie temperature of different compositions. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cation distribution; Curie temperature; Electron microscopy; Magnetization; Spinel ferrite